Sustainable thermal buffering of microencapsulated bio-phase change materials through an engineered biochar dopant - Dimberu G. Atinafu; Ji Yong Choi; Jihee Nam; Beom Yeol Yun; Sumin Kim (Biochar)
Abstract Climate change and unbalanced energy demand and consumption require innovative approaches to the development of sustainable and renewable energy technologies. Phase change materials (PCMs) present exceptional solutions for zero-energy thermal management due to their outstanding energy storage density at an isothermal phase transition. However, the low thermal transport and thermal stability of bulk PCMs, as well as the expensive and complex synthesis of additive materials, hinder their large-scale utilization. In this study, food-waste-derived engineered biochar (FW) is produced via slow pyrolysis to improve the thermal properties of a microencapsulated bio-PCM (B28). The thermal performance of biochar-PCM composites is evaluated based on two biochar preparation systems: varying activation temperatures (carbonized at 400 °C followed by KOH activation at different temperatures (500–800 °C)) and varying mass ratios between KOH and biochar. The introduction of a low (0.63 wt%) engineered biochar dopant significantly improves the thermal diffusivity of B28 by more than 1.3-fold. The biochar-PCM microcapsule composites present fusion and crystalline isothermal phase transition temperatures of 29.4 ± 0.38 °C and 16.7 ± 0.13 °C, respectively. Moreover, the bio-PCM exhibits a highly efficient energy per unit mass of 61.6 kJ kg–1, which is 101.7% of the energy storage capacity of bulk B28. Additionally, the composite demonstrates high thermal stability with decomposition occurring above 195 °C, thus enabling an increase of > 20 °C in the onset decomposition point compared with pristine B28. Further analysis reveals the impact of the KOH/biochar mass ratio on the thermal properties of bio-PCM. Sample FW6PCM, in which the biochar is activated at 600 °C with a KOH/biochar mass ratio of 1, exhibits the highest enthalpy storage capacity. This study suggests a promising strategy for designing high-performance, eco-friendly, and scalable bio-based composite PCMs by overcoming the long-standing bottleneck of microcapsules, which is crucial for advanced thermal management applications such as cooling and green buildings. Graphical Abstract